Security council resolution 2669 (2022) on the situation in Myanmar: too little, too late? - Hamid, Abdul Ghafur@Khin Maung Sein (Oxford University Press (OUP), 2023)
On December 21, 2022, the United Nations Security Council adopted Resolution 2669 (2022) on the situation in Myanmar. This is the first-ever Security Council resolution on Myanmar, nearly two years after the military coup d’etat on February 1, 2021. This is a long overdue resolution that the people of Myanmar have eagerly awaited. However, it does not call for the implementation of R2P. It was not adopted as an enforcement action under Chapter VII of the Charter. There can be no enforcement action against non-compliance. the unprecedented UN Security Council resolution on Myanmar can be taken as a small but significant step forward. It can hopefully be followed by further and stronger resolutions in the future.